Pedagogical Renewal to Achieve Peace Education Curriculum: Artificial Intelligience as Path in Nigeria - Ojo, Erinsakin Martins; Damilola, Olaniyan Olaolu (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The study investigates pedagogical renewal to achieve a peace education curriculum through the integration of artificial intelligence (AI) in Nigerian universities. Despite the critical role of peace education in fostering national stability, traditional teaching methods often struggle to engage students effectively in the digital age. This study aimed to explore how AI can serve as a transformative path for pedagogical renewal in this field. A descriptive survey research design was employed, focusing on a population of peace education lecturers. Using a purposive sampling technique, a sample size of 180 respondents was selected. Data were collected via a self-structured instrument titled "Questionnaire on Pedagogical Renewal to Achieve Peace Education: Artificial Intelligence as Path in Nigeria (QPRAPEIAPN)," which utilized a four-point Likert scale. The instrument was validated by experts in measurement and evaluation, achieving a reliability coefficient of 0.72 through the test-retest method. Data were analyzed using descriptive statistics, including simple percentages, frequency counts, and mean scores. The results revealed that AI significantly enhances the efficiency of lesson planning and the delivery of peace education, offering personalized and interactive learning experiences. Consequently, it was concluded that AI is a viable tool for revitalizing the curriculum. The study contributes to the field by providing empirical evidence for digital transformation in social sciences. Based on these findings, it is recommended that universities prioritize the provision of AI infrastructure and implement mandatory AI literacy programs for educators to ensure a seamless pedagogical transition.